AB0925 Liver Involvement in Adult Onset Still's Disease: Retrospective Analysis of 18 Cases. (10th June 2014) - Ferro, F.; Cioffi, E.; Elefante, E.; Parma, A.; Cazzato, M.; Della Rossa, A.; d'Ascanio, A.; Mazzantini, M.; Neri, R.; Baldini, C.; Bombardieri, S.
Abstract : Background: Adult-onset Still's disease (AOSD) is a multisystem inflammatory disease of unknown etiology typically characterized by high fever, arthralgias/arthritis and transient cutaneous rash. Liver involvement has been reported in AOSD, however only few studies have described it comprehensively. Objectives: To describe the frequency and clinical presentation of liver involvement in a single center cohort of AOSD. Methods: Retrospective observational study including unselected patients with a diagnosis of AOSD made according to the Yamaguchi criteria and admitted at our University Hospital between 2009 and 2013. Demographic, clinical and serological data were retrieved from patients files including: fever, evanescent rash, sore throat, arthritis, myalgias, pleuritis, pericarditis, pneumonitis, lymphadenopathy, splenomegaly, hepatomegaly leucocytosis >15, 000/μl and high serum ferritin levels. The severity of liver-associated enzymes was based on the degree of elevation and was stratified as mild (<2 times normal), moderate (2-5 times normal), and severe (>5 times normal). Severe liver dysfunction was defined as having all of the following criteria: total bilirubin >3 mg/dL; albumin <3.2 g/dL; and prothrombin time >3 seconds prolonged. Medications used, response to treatment and long-term outcomes were also recorded. Comparison in terms of continuous data were determined using independent sample t tests or Mann–Whitney tests, and in terms of proportions using contingency table analysis and chi square test. Results: Eighteen patients (9 F: 9M; mean age (SD) =37 (12) years, mean follow-up=31 (15) months) were included in the study. Twelve patients out of 18 (66.6%) presented liver test abnormalities whereas hepatomegaly occurred in 4/18 (22.2%) cases. No correlation was found between liver involvement and gender or age at the diagnosis. A mild elevation of liver enzymes was found in 4/12 cases, a moderate alteration in other 4 patients, and a severe cytolysis in the other 4. A liver biopsy was performed in 3/12 patients revealing acute hepatitis with necrosis and accompanying non specific inflammatory infiltration. Three patients presented a liver acute failure concurrently with a diffuse intravascular coagulation (DIC) and, in one case, with a fatal macrophagic activation syndrome (MAS). Prednisone therapy induced a fast improvement of liver function in all the cases but one. Hydroxychloroquine, methotrexate and cyclosporine were the most common steroid sparing agents adopted during the follow-up. Conclusions: Our findings outlined the high frequency of liver involvement in AOSD. Despite generally mild or moderate, severe acute hepatitis can occur during the disease course especially in those patients with DIC or MAS features. Treatment with systemic corticosteroid therapy is generally able to control liver function during AOSD, however steroid sparing agents are crucial in maintaining a long- term remission. Larger prospective studies could clarify the pathogenetic role of macrophagic activation in AOSD severe liver involvement, leading to develop new concepts for treatment modalities. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4541